Physical and fitness characteristics of elite professional Rugby Union players - Posthumus, L.; Macgregor, C.; Winwood, P.; Darry, K.; Driller, M.; Gill, N. (Sports, 2020)
This study explored the physical and fitness characteristics of elite professional rugby union players and examined the relationships between these characteristics within forwards and backs. Thirty-nine elite professional rugby union players from the New Zealand Super Rugby Championship participated in this study. Body composition was measured using dual-energy X-ray absorptiometry alongside anthropometrics. Fitness characteristics included various strength, power, speed, and aerobic fitness measures. Forwards were significantly (p = 0.01) taller and heavier than backs, and possessed greater lean mass, fat mass, fat percentage, bone mass, and skinfolds. Forwards demonstrated greater strength and absolute power measures than backs (p = 0.02), but were slower and possessed less aerobic fitness (p = 0.01). Skinfolds demonstrated very large correlations with relative power (r = -0.84) and speed (r = 0.75) measures within forwards, while backs demonstrated large correlations between skinfolds and aerobic fitness (r = -0.54). Fat mass and fat percentage demonstrated very large correlations with speed (r = 0.71) and aerobic fitness (r = -0.70) measures within forwards. Skinfolds, fat mass, and fat percentage relate strongly to key fitness characteristics required for elite professional rugby union performance. Individual and positional monitoring is important due to the clear differences between positions.